2016
DOI: 10.1016/j.jsams.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

95% prevalence of abnormality on hip MRI in elite academy level rugby union: A clinical and imaging study of hip disorders

Abstract: The prevalence of abnormality on MRI of the hip is high in rugby players at 95% of study participants. The percentage reporting symptoms was lower at 65% of the cohort although this was significantly higher than (non-rugby) matched controls at 15% of participants. Rugby players demonstrated significantly reduced ROM of the hip compared to controls. Further prospective research is required to investigate the long term sequelae of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…In total, 375 (28%) of the athletes were women and 960 were men. The included studies investigated different sports including American football (n=174) [62,49], soccer (n=100) [57,53], ice hockey (n=179) [64,58,59,48], ballet (n=110) [65,52,66,50,63], rugby (n=20) [55], golf (n=55) [67], skiing (n=27) [58], track and field (n=22) [56], capoeira (n=24) [51] and mixed sports (n=624) [65,52,66,61,54,60]. The level of play reported in the included studies included professional [63,65,52,66,50,59,64,61], elite [56,48,67,55,54,49,62,59], semi-professional [57], amateur or recreational [57,65,52,66,61] and youth/high school level…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 375 (28%) of the athletes were women and 960 were men. The included studies investigated different sports including American football (n=174) [62,49], soccer (n=100) [57,53], ice hockey (n=179) [64,58,59,48], ballet (n=110) [65,52,66,50,63], rugby (n=20) [55], golf (n=55) [67], skiing (n=27) [58], track and field (n=22) [56], capoeira (n=24) [51] and mixed sports (n=624) [65,52,66,61,54,60]. The level of play reported in the included studies included professional [63,65,52,66,50,59,64,61], elite [56,48,67,55,54,49,62,59], semi-professional [57], amateur or recreational [57,65,52,66,61] and youth/high school level…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five studies (4 MR and 1 HR) [48,57,55,58,59] reported the prevalence of labral tears per person in asymptomatic athletes. Limited evidence from 4 studies (4 MR) [48,55,58,57] identified a labral tear prevalence of 54% (95%CI 22% to 83%) per person (Figure 2). The remaining study (HR) [59] reported a labral tear prevalence of 56% in ice hockey players competing at professional and collegiate level respectively.…”
Section: Asymptomatic Participantsmentioning
confidence: 99%
See 3 more Smart Citations